O desejo de navegar e as âncoras na tradição: memória e identidade de Daniel Munduruku - Barros, Ivanilde de Lima (2014)
The purpose of this paper is to analyze how is the redefinition of memory in the Daniel Munduruku‟s works Meu vô Apolinário: um mergulho no rio da (minha) memória e Você lembra, pai?, seeking to understand the extent to which intervenes in the representations of identities that seek to ratify the tradition and ancestry. Munduruku is the most renowned Indian writer in the Brazilian literary scene today, with 45 published works, is representative of an indigenous writing that, although at different stages, is conquering space and increasingly being published in Brazil, opening up a new range for cultures underrepresented in fiction from the point of view of indigenous own. The voice silenced before the colonists constitutes, in the literary sphere, the representation of what is being indigenous. This tell if states by navigating the river of memory, and search in a North ancestry that point cultural aspects that can sustain an indigenous identity ideal, taking the difference as contrasting and constituent brand. When looking at the past to explain the present, the anchors of literary craft are launched at certain points, discontinuing the movement in the waters of memory. These issues will be addressed in this study essentially qualitative, whose foundations are based on the theoretical framework of interdisciplinary research on identity-memory-representation, in which were involved knowledge of Sociology, Anthropology and Social Psychology, standing in the quest for understanding the influences what is recollected in indigenous works, and social representations that dominate as identity marks, or the identity.